Analisis Standar Pendidik dan Tenaga Kependidikan di Sekolah Dasar Negeri Sidoarjo - Muhlasin Amrullah; Nur Lailatul Khasanah; Mahardika Darmawan Kusuma wardana; Khizanatul Hikmah (Jurnal Pendidikan Edutama, 2023)
Abstract: This article describes the achievement of educator and education personnel standards at SDN 2 Sidoarjo as a pilot school. This type of research is qualitative research with a case study approach, conducted by obtaining primary and secondary data from observation, interviews and documentation. The research subjects were the principal, 21 teachers and 4 education personnels at SDN 2 Sidoarjo. Data analysis techniques used data reduction models, data presentation and drawing conclusions or verification that developed by Miles and Huberman. The results obtained are the analysis of the standards of educators and education personnel at SDN 2 Sidoarjo has met the standards of educators and education personnel based on the Regulation of the Minister of National Education of the Republic of Indonesia No.13 of 2007. However, there are findings that some educators still have a diploma or high school education but these educators are currently in the process of obtaining a bachelor's degree or S1 PGSD / PGMI in accordance with applicable educator standards, the role of principals in Improvement of Human Resources through further study, professional training and continuing to upgrade the skills of educators and education personnel, the pattern of leadership management of school coconuts is very decisive in meeting national education standards. Keywords: analysis, teacher, education personal, SDN 2 Sidoarjo Abstrak: Artikel ini mendeskripsikan ketercapaian standar pendidik dan tenaga kependidikan di Sekolah Dasar Negeri 2 Sidoarjo sebagai sekolah percontohan. Jenis penelitian ini adalah penelitian kualitatif dengan pendekatan studi kasus, dilakukan dengan mendapatkan data primer dan sekunder dari observasi, wawancara dan dokumentasi. Subjek penelitian adalah kepala sekolah, 21 guru dan 4 tenaga kependidikan di SD Negeri 2 Sidoarjo. Teknik analisis data menggunakan model reduksi data, penyajian data dan menarik kesimpulan atau verifikasi yang dikembangkan oleh Miles dan Huberman. Hasil yang diperoleh adalah analisis standar pendidik dan tenaga pendidikan di SD Negeri 2 Sidoarjo telah memenuhi standar pendidik dan tenaga kependidikan berdasarkan Peraturan Menteri Pendidikan Nasional Republik Indonesia No.13 Tahun 2007 Namun terdapat temuan beberapa tenaga pendidik masih memiliki ijazah atau pendidikan terakhir SMA akan tetapi tenaga pendidik tersebut saat ini sedang berproses untuk mendapatkan ijazah sarjana atau S1 PGSD/PGMI sesuai dengan standar tenaga pendidik yang berlaku, peran kepala sekolah dalam Improvement Of Human Resources melalui study lanjut, pelatihan keprofesian dan terus melakukan upgrading skill tenaga pendidik dan tenaga kependidikan, pola managemen kepemimpinan kelapa sekolah sangat menentukan dalam pemenuhan standar nasional pendidikan . Kata Kunci: analisis, tenaga pendidik, tenaga kependidikan, SDN 2 Sidoarjo